10.1093/gao/9781884446054.013.7002292402 (Inactive DOIs, 2018)
INTRODUCTION: Tafamidis has been demonstrated to improve survival and quality of life in transthyretin amyloid cardiomyopathy (ATTR-CM). However, its cost-effectiveness has been reported to exceed the threshold of $100,000/quality-adjusted life years [QALY] in the US healthcare system. This study aimed to evaluate costs associated with utilities (QALYs) gained for ATTR-CM in France, Spain, Germany, and the United Kingdom (UK), and to conduct a deterministic modelling study using case-scenarii based on various assumptions at a European level. METHODS: Data on costs and QALY were extracted using MEDLINE. The lack of data on the cost of the cardiac amyloidosis in patients treated with tafamidis led us to modelling our study based on heart failure assumptions. We used QALY gained in the tafamidis group as reported for ATTR-CM patients in the ATTR-ACT trial to determine the incremental cost-effectiveness ratio (ICER) of tafamidis compared with standard care. A sensitivity analysis was conducted with assumptions on costs and QALYs gained. RESULTS: Incremental cost-effectiveness ratios (ICER) for each country largely exceeded the threshold of €100,000/QALY, ranging from €398,136/QALY gained in France to €1,398,706/QALY gained in Germany. The sensitivity analysis revealed large variations of the ICER, with only 27.4%, 0.2%, 13% and 9% probability of cases below the acceptability threshold of €100,000/QALY in France, Spain, Germany and UK, respectively. CONCLUSION: While tafamidis offers a significant improvement in patients' quality of life and survival, these exploratory scenario-based estimates showing high cost-effectiveness ratio in some European countries, may raise public health and cost management concerns.